Pengaruh Kepribadian dan Konsep Diri Terhadap Keputusan Pembelian Produk Lazada - Hasrudy Tanjung; Irwan Syari Tanjung; Salsabila Safitri (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The purpose of this study was to determine and analyze the influence of personality, and self-concept on product purchasing decisions at Lazada partially or simultaneously. The approach used in this research is an associative approach. The population in this study were all students of the Faculty of Economics and Business, Muhammadiayah University, North Sumatra in 2018, 2019 and 200 who bought products at Lazada. The sample in this study used the Slovin Sempling formula, amounting to 95 students of the Faculty of Economics and Business, Muhammadiayah University of North Sumatra who bought lazada products. The data collection techniques in this study used interview techniques, documentation study, observation, and questionnaires. The data analysis technique in this study used the Multiple Liner Regression Analysis Test, Hypothesis Test (t test), and the Coefficient of Determination. Data processing in this study used the SPSS (Statistical Package for the Social Sciens) software program version 24.00. The results of this study prove that partially personality, and self-concept of the purchase decision for lzada products.